Designing An Application for Recording Data on Incoming and Outgoing Medicines Using the First In, First Out Method: Case Study at One Health Service Center in Bandung Regency - Achyar Nuraulia Rahman; Asep Ririh Riswaya (Electronic, Business, Management and Technology Journal, 2023)
The health service center in Bandung Regency is a place for taking medicine for sick residents. The pharmacy is responsible for procuring, ordering, receiving, storing, distributing, recording, and reporting medicine supplies. The series of drug data processing activities for health services starts from ordering drugs, collecting drug data, dispensing drugs, and recording and reporting. To make it easier to record transactions and report drug supplies, a particular application based on PHP programming and a MySQL database was created, which is expected to assist in recording drug purchase and sale transactions, as well as creating reports so that it can further increase the effectiveness of work at pharmacies in providing services, towards citizens.